2022
DOI: 10.1001/jamanetworkopen.2021.44039
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Onset-to-Treatment Time With Discharge Destination, Mortality, and Complications Among Patients With Aneurysmal Subarachnoid Hemorrhage

Abstract: IMPORTANCE Rapid access to specialized care is recommended to improve outcomes after aneurysmal subarachnoid hemorrhage (SAH), but understanding of the optimal onset-to-treatment time for aneurysmal SAH is limited. OBJECTIVE To assess the optimal onset-to-treatment time for aneurysmal SAH that maximized patient outcomes after surgery. DESIGN, SETTING, AND PARTICIPANTSThis cohort study assessed 575 retrospectively identified cases of first-ever aneurysmal SAH occurring within the referral networks of 2 major te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Based on the results of the statistical analysis, we believe that the timing of endovascular treatment is an independent predictor of the prognosis of high-grade aneurysm. The receiver operating characteristic (ROC) curve suggests that the optimal timing of endovascular therapy is 12.5 h after onset, which is similar to the findings of Buscot et al (30). However, their study included patients of all grades.…”
Section: Discussionsupporting
confidence: 79%
“…Based on the results of the statistical analysis, we believe that the timing of endovascular treatment is an independent predictor of the prognosis of high-grade aneurysm. The receiver operating characteristic (ROC) curve suggests that the optimal timing of endovascular therapy is 12.5 h after onset, which is similar to the findings of Buscot et al (30). However, their study included patients of all grades.…”
Section: Discussionsupporting
confidence: 79%
“…83 Case-fatality rates in aSAH have declined over the past 2 decades, attributed to improved medical and surgical care and the emergence of neurocritical care units. 74 In the PRINCE study (Point Prevalence in Neurocritical Care) of 257 centers in 47 countries, variability in the delivery of neurocritical care to patients with various neurological emergencies is present worldwide; severity of illness and absence of a dedicated neurocritical care unit were independent predictors of mortality. 78,79 Although some studies describe superior outcomes at hospitals that take care of more patients with aSAH, other studies do not find this relationship.…”
Section: Recommendations For Hospital Characteristics and Systems Of ...mentioning
confidence: 99%
“…Philips et al ( 13 ) demonstrated that in their mixed surgical and endovascular series, the patients treated within 24 h after symptom onset had a better clinical outcome at 6 months. These data were confirmed by Consoli et al ( 14 ), who demonstrated that hyper-early endovascular treatment within 12 h after SAH is not associated with a lower morbidity or a better clinical outcome with respect to treatment after 12 h. Recently, Buscot et al ( 15 ) and Wu et al ( 16 ) showed that best clinical outcomes were achieved treating the patients at ~12.5 h.…”
Section: Introductionmentioning
confidence: 65%